Aplikace metody SNP array v prenatální diagnostice - Becvárová, V; Hynek, M; Putzová, M; Soldátová, I; Horácek, J; Smetanová, D; Kulovaný, E; Matousková, M; Krutílková, V; Hlavová, E; Rasková, D; Hejtmánková, M; et al. (Ceska gynekologie, 2011)
OBJECTIVES: SNP array (array method using Single Nucleotide Polymorphisms) enables to detect cytogenetically undetectable submicroscopic alterations (microdeletions, microduplications), which could be also causative for ultrasonographic anomalies of fetus. This article describes the principle, advantages, disadvantages and application possibilities of the SNP array method in prenatal diagnosis. The ten month experience with SNP array use in prenatal diagnosis is presented. DESIGN: Prospective study. SETTINGS: Gennet, Prague. MATERIAL AND METHODS: During the period from April 2010 to January 2011 we performed 110 SNP array analyses of fetal DNA: 14 chorionic villi samples (CVS), 88 amniotic fluid samples (AMC), 1 cord blood sample and 7 miscarriage samples. Laboratory tests were carried out on DNA from both cultured and uncultured fetal cells. Examinations were performed in fetuses with sonographic abnormal findings having normal karyotype. In addition 14 fetal cytogenetic abnormalities were solved. SNP array analysis was performed using Illumina InfiniumHD HumanCytoSNP-12 chip. All data were analysed by Illumina KaryoStudio and GenomeStudio software. RESULTS: SNP array analysis was performed in 108 fetuses (only 2 examination failures, 1.8%). In total, we detected CNV (copy number variation) in 29 samples (29/108 = 27%). 15% (16/108) of fetuses with abnormal ultrasound findings were found to carry clinically relevant CNV. Probably benign CNVs were found in 8 samples (8/108 = 7%) and in additional 5 CNVs parental samples have not been analysed yet. Excluding karyotypically abnormal cases clinically relevant CNVs were found in 10% of fetuses (9/94). In all cases with de novo chromosomal aberration the clinical relevancy was clarified (imbalances in 50%). CONCLUSION: Our data suggest that SNP array analysis is a relevant and useful technique in prenatal diagnosis.
Keywords: Congenital Abnormalities; Pregnancy; Polymorphism, Single Nucleotide; lidé; vrozené vady; prenatální diagnóza; ultrasonografie prenatální; Oligonucleotide Array Sequence Analysis; Ultrasonography, Prenatal; Prenatal Diagnosis; ženské pohlaví; Humans; jednonukleotidový polymorfismus; Female; těhotenství; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů